2013
DOI: 10.5194/acpd-13-17299-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feldspar minerals as efficient deposition ice nuclei

Abstract: Mineral dusts are well known to be efficient ice nuclei, where the source of this efficiency has typically been attributed to the presence of clay minerals such as illite and kaolinite. However, the ice nucleating abilities of the more minor mineralogical components have not been as extensively examined. As a result, the deposition ice nucleation abilities of 24 atmospherically-relevant mineral samples have been studied, using a continuous flow diffusion chamber at −40.0 ± 0.3 °C. The same particl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…First, although cooled SOA‐WSOC particles were found to be IN in the deposition nucleation mode, their S 0.1% values are still somewhat higher than those of other materials recognized as efficient IN. For example, using exactly the same experimental approach, our group has recently studied several mineral dust particles such as Arizona test dust, Mojave Desert dust, and feldspar‐containing substrates and shown that they are able to nucleate ice via deposition nucleation at S 0.1% values between 1.30 and 1.40 at temperatures similar to this study [ Yakobi‐Hancock et al , ]. Similarly, the review of Hoose and Möhler [] has demonstrated that many other materials, including Snomax and solid AS, can nucleate ice via deposition nucleation at low ice supersaturations and low temperatures.…”
Section: Conclusion and Atmospheric Implicationssupporting
confidence: 74%
“…First, although cooled SOA‐WSOC particles were found to be IN in the deposition nucleation mode, their S 0.1% values are still somewhat higher than those of other materials recognized as efficient IN. For example, using exactly the same experimental approach, our group has recently studied several mineral dust particles such as Arizona test dust, Mojave Desert dust, and feldspar‐containing substrates and shown that they are able to nucleate ice via deposition nucleation at S 0.1% values between 1.30 and 1.40 at temperatures similar to this study [ Yakobi‐Hancock et al , ]. Similarly, the review of Hoose and Möhler [] has demonstrated that many other materials, including Snomax and solid AS, can nucleate ice via deposition nucleation at low ice supersaturations and low temperatures.…”
Section: Conclusion and Atmospheric Implicationssupporting
confidence: 74%
“…Recently Atkinson et al 24 performed the first comparative study on ice nucleation in the immersion mode looking not only at single minerals from the clay group but also at K-feldspar, Na/Ca-feldspar, quartz, and calcite as well. Almost simultaneously Yakobi-Hanock et al 25 conducted a similar study on ice nucleation of 24 mineral samples in the deposition mode. Both studies find the ice nucleating ability of K-feldspar exceptionally high compared to other minerals.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, our observations show that the acid treatment caused structural deformation or disorderliness in four dust test samples (ATD, illite, montmorillonite, and K‐feldspar) (Figure and Table ), but the acid treatment did not modify the structural properties of the quartz particles (Figure S1 and Table ). Acid treatment affected the K‐feldspar group minerals (albite, orthoclase, and anorthite; Figure ), which are suggested to be the important ice nucleating minerals for atmospheric ice nucleation [ Atkinson et al ., ; Yakobi‐Hancock et al ., ]. The peak intensities of the orthoclase and albite minerals were reduced in ATD, whereas the orthoclase from illite was completely lost.…”
Section: Resultsmentioning
confidence: 99%